2016
DOI: 10.1542/hpeds.2015-0251
|View full text |Cite
|
Sign up to set email alerts
|

Directly Comparing Handoff Protocols for Pediatric Hospitalists

Abstract: The results suggest that Flex 11 is an efficient, beneficial tool in a simulated environment with pediatric clinicians. Future studies should evaluate this protocol in the inpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Handoff protocol Flex 11 has been studied and compared with SBAR communication tool; overall, there was no difference in workload, the amount of information required for handoff, and duration of handoff except Flex 11 was rated high for "ease of use" and "being helpful" as compared to SBAR tool [65].…”
Section: Comparison Of Sbar With Other Communication Toolsmentioning
confidence: 99%
“…Handoff protocol Flex 11 has been studied and compared with SBAR communication tool; overall, there was no difference in workload, the amount of information required for handoff, and duration of handoff except Flex 11 was rated high for "ease of use" and "being helpful" as compared to SBAR tool [65].…”
Section: Comparison Of Sbar With Other Communication Toolsmentioning
confidence: 99%
“…Simulation has been used to evaluate handoffs by third-year medical students 28 and in pediatrics. 29 We observed an even greater deterioration in information retention than reported in those studies, possibly because our clinical scenario was more complex. Clinical trials have shown that use of checklists for transitions between operating room and intensive care unit 30 and between operating room and post-anesthesia care unit, 31 result in a greater number of items transferred that are deemed “must” and “should” be handed over, further reporting that essential clinical information may not be adequately conveyed without a formalized tool or process.…”
Section: Discussionmentioning
confidence: 46%
“…In healthcare, there has been a growing interest in measuring SMMs through methods like card sorting to understand their impact on areas such as the integration of healthcare organizations, 26 collaboration of clinical teams, 27 and implementation of clinical guidelines. 28 Card sorting has been employed to show significant differences between mental models among healthcare team members, 29,30 as well as demonstrated how disparate mental models impact computerized decision aids design, 31 clinical team performance, 32 and the development of clinical handoff tools. 33 This particular method of elicitation may be helpful within the context of healthcare for understanding differences in role expectations or policy perceptions between disciplines, professions, or levels of tenure.…”
Section: Card Sortingmentioning
confidence: 99%